PENGELOLAAN PEMBELAJARAN PENDIDIKAN ANAK USIA DINI (PAUD) DI KB “CERDAS” KECAMATAN SUKOREJO KABUPATEN KENDAL - Rosyid Ridho; Markhamah Markhamah; Darsinah Darsinah (Jurnal Penelitian Humaniora, 2015)
The purpose of this study was to determine (1) Early Childhood Lesson Planning in KB Cerdas Sukorejo Kendal, (2) implementation of learning, (3) Assessment of learning. This research is qualitative. The research was carried out in KB Cerdas Sukorejo Kendal. The main subject of the study was the Chief Manager, teacher, and students. The methods of the data collection to make use of in-depth interviews, observation, and documentation. Analysis of the data to begin with : Data Collection, data reduction, data display, and conclusion. the validity of the data using the credibility, and triangulation. The results of this study are (1) Lesson planning in KB Cerdas Sukorejo have done by developing programs of activities for a year through the semester planning,   weekly activities planning (RKM), and daily activities planning (RKH), taking into account the level of development, necessary, interests, and characteristics of the child, and also the aspects of development religious values and moral, cognitive, motor, language and social-emotional, (2) Implementation of Learning in KB Cerdas Sukorejo to begin a) with happy morning, b) activities of habituation, c) transitions, d) footing environment, e) footing before playing, f) footing while playing g) footing after playing h) introduction praying, and i) closing prayer. Learning was refer to the implementation of the principle of learning while playing with the approach of beyond center and circle time (BCCT), the method of question and answer, and role play by arrangement of conducive play house, to creates a comfortable condition to play, safe, clean, healthy and interest, the use of educational games was standards, as well as take advantage of the learning environment at the institution. (3) Assessment of learning is done by observation every times not only when the children play in the center, but it begin from the reception children, while teaching and Learning process  until the study is finished through the performance of the child, the child’s assignment, with the development of indicators of the level of achievement which covers five aspects of the development of the students. Assessment techniques in KB Cerdas learning through observation, anecdotal and portfolio.